(3GdefbP ef GdgdcI aj OaY eVGQ GdSehe GdegdcIs - (3GdMSf Hf CHj JZdH Hf GdeHGQc Hf CHj GdTQa, GdeJWHHs
(3ChdgG (B:s
(3HYO GdMeO ddg bGd GdMSjf Hf CHj JZdH Ef GdfYeI JRQY GdeMHI hcGf GdeTab dGjRGd ecdakG s
(3BNQgG (B:s
(3hjNdW eY eKdg YjT de jUjHg fGQ hjUeO ehVY GdYVg aEfg fGaY Ef TGA Gddg s
(3fSNI CNQi NRGFfjIs
(3ePgHI GdWGdY hGdYfGhjfs
(3HQSe Gdedc GdCTQa TYHGf Hf MSjf Hf Gdedc GdfGUQ eMeO Hf bdGhhfs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs